DiPALS: diaphragm pacing in patients with amyotrophic lateral sclerosis - a randomised controlled trial - McDermott, C; Bradburn, M; Maguire, C; Cooper, C; Baird, W; Baxter, S; Cohen, J; Cantrill, H; Dixon, S; Ackroyd, R; Baudouin, S; Bentley, A; et al. (NIHR Health Technology Assessment Programme, 2016)
Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disease resulting in death, usually from respiratory failure, within 2-3 years of symptom onset. Non-invasive ventilation (NIV) is a treatment that when given to patients in respiratory failure leads to improved survival and quality of life. Diaphragm pacing (DP), using the NeuRx/4(®) diaphragm pacing system (DPS)™ (Synapse Biomedical, Oberlin, OH, USA), is a new technique that may offer additional or alternative benefits to patients with ALS who are in respiratory failure.The Diaphragm Pacing in patients with Amyotrophic Lateral Sclerosis (DiPALS) trial evaluated the effect of DP on survival over the study duration in patients with ALS with respiratory failure.The DiPALS trial was a multicentre, parallel-group, open-label, randomised controlled trial incorporating health economic analyses and a qualitative longitudinal substudy.Eligible participants had a diagnosis of ALS (ALS laboratory-supported probable, clinically probable or clinically definite according to the World Federation of Neurology revised El Escorial criteria), had been stabilised on riluzole for 30 days, were aged ≥ 18 years and were in respiratory failure. We planned to recruit 108 patients from seven UK-based specialist ALS or respiratory centres. Allocation was performed using 1 : 1 non-deterministic minimisation.Participants were randomised to either standard care (NIV alone) or standard care (NIV) plus DP using the NeuRX/4 DPS.The primary outcome was overall survival, defined as the time from randomisation to death from any cause. Secondary outcomes were patient quality of life [assessed by European Quality of Life-5 Dimensions, three levels (EQ-5D-3L), Short Form questionnaire-36 items and Sleep Apnoea Quality of Life Index questionnaire]; carer quality of life (EQ-5D-3L and Caregiver Burden Inventory); cost-utility analysis and health-care resource use; tolerability and adverse events. Acceptability and attitudes to DP were assessed in a qualitative substudy.In total, 74 participants were randomised into the trial and analysed, 37 participants to NIV plus pacing and 37 to standard care, before the Data Monitoring and Ethics Committee advised initial suspension of recruitment (December 2013) and subsequent discontinuation of pacing (on safety grounds) in all patients (June 2014). Follow-up assessments continued until the planned end of the study in December 2014. The median survival (interquartile range) was 22.5 months (lower quartile 11.8 months; upper quartile not reached) in the NIV arm and 11.0 months (6.7 to 17.0 months) in the NIV plus pacing arm, with an adjusted hazard ratio of 2.27 (95% confidence interval 1.22 to 4.25; p = 0.01).Diaphragmatic pacing should not be used as a routine treatment for patients with ALS in respiratory failure.It may be that certain population subgroups benefit from DP. We are unable to explain the mechanism behind the excess mortality in the pacing arm, something the small trial size cannot help address. Future research should investigate the mechanism by which harm or benefit occurs further. Current Controlled Trials ISRCTN53817913.